Evaluation of growth and puberty in a child with a novel TBX19 gene mutation and review of the literature - BEREKET, ABDULLAH; ELTAN, MEHMET; KAYGUSUZ, SARE BETÜL; DEMİRCİOĞLU, SERAP; KIRKGÖZ, TARIK; GÜRAN, TÜLAY (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
Background Biallelic mutations in the TBX19 gene cause severe early-onset adrenal failure due to isolated ACTH deficiency (IAD). This rare disease is characterized by low plasma ACTH and cortisol levels, with normal secretion of other pituitary hormones. Herein, we report a patient with IAD due to a novel TBX19 gene mutation, who is also of tall stature. Case report A 4(8/12)-year-old girl was presented with loss of consciousness due to hypoglycemia. The patient was born at term with a birth weight of 3800 g. Her parents were first-degree cousins. She had a history of several hospitalizations for recurrent seizures, abdominal pain, and vomiting. At presentation, her weight and height were + 1.8 and + 2.2 SDS, respectively. Serum glucose was 25 mg/dl (1.4 mmol/L), with normal sodium, potassium, and insulin concentrations. The child was hypocortisolemic (0.1 mu g/dl), and ACTH levels were extremely low (< 5.0 pg/ml). A diagnosis of IAD was made and hydrocortisone treatment was started. Hypoglycemic episodes, seizures, and recurrent gastrointestinal complaints disappeared after hydrocortisone replacement. Magnetic resonance imaging of the pituitary was normal. Whole exome sequencing revealed a novel homozygous c.302G > A (W101*) mutation in the TBX19 gene. Conclusion We report a new mutation in the TBX19 gene in a patient with isolated ACTH deficiency. While overgrowth is a known feature of some types of adrenal insufficiencies, including MC2R gene defects and POMC deficiency, it may be a novel feature for TPIT deficiency, as in our patient.
Keywords: TPIT; TBX19; Isolated ACTH deficiency; Growth; Puberty; Central adrenal insufficiency; POMC-DEFICIENCY; ADRENOCORTICOTROPIN DEFICIENCY; TPIT MUTATIONS; EARLY-ONSET; DIAGNOSIS; ESTRIOL; TYPE-1; RESISTANCE; PATIENT